HydroMoth as a tool for quantitative underwater SPL measurements in benthic ecological research - Til Böttner; René Ortmann; Farhan Pasolong; Wolfgang H. Kirchner; Stefan Herlitze; Mareike Huhn (PLoS ONE, 2026)
Quantitative passive acoustic monitoring in benthic settings requires conversion of recorded amplitudes into absolute sound pressure levels (SPL, dB re 1 µPa). We tested whether HydroMoth (HM) recorders can provide sufficiently accurate SPL estimates in the low-frequency band relevant to benthic marine invertebrates and ship noise. Nine units were calibrated by a single-point offset using a 1000 Hz reference tone in an anechoic chamber and subsequently compared to a factory-calibrated SoundTrap ST600 in a controlled playback experiment (100–1000 Hz). In the pool dataset (HM1–HM5), deviations ranged from −2.6 to +1.8 dB with mean absolute errors typically within ~1–3 dB across frequencies; field measurements (HM6–HM9) showed deviations of similar magnitude, with mean deviations ranging from −0.5 to +1.0 dB across frequencies and mean absolute errors between 0.9 and 2.4 dB. Device orientation was fixed and identical across setups, reflecting benthic use cases where orientation is constrained and orientation related sensitivity differences act as a constant factor within deployments. These results show that HydroMoth recorders, under defined benthic conditions and within 100–1000 Hz, can provide SPL estimates with deviations comparable to those observed between commercial reference systems. This enables quantitative use of low-cost recorders in applications where absolute accuracy within a few decibels is sufficient.